2021
DOI: 10.17159/2413-3051/2021/v32i3a9403
|View full text |Cite
|
Sign up to set email alerts
|

moderating and mediating role of local government in the community engagement strategy of a renewable energy company in South Africa

Abstract: Adopting a qualitative case study approach of a renewable energy company in South Africa, the research investigated community engagement within the tripartite relationship of a wind farm, the communities, and the local government. It was found that local government played a moderating role in the community engagement efforts of the wind farm which had to comply with certain engagement protocols determined by local government. Local government also played a mediating role in corporate community engagement, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In Africa, community engagement in global health research has been influenced by structural coercion, highlighting the importance of ethical and culturally sensitive approaches (Nyirenda et al, 2020). Furthermore, a qualitative case study approach of a renewable energy company in South Africa investigated community engagement within the tripartite relationship of a wind farm, the communities, and the local government, emphasizing the significance of collaboration between the private sector, communities, and local government (Robinson & Stephens, 2021). In the USA, communityengaged research experiences in rural communities have demonstrated the integration of collaborative governance for community solar projects, showcasing the practical application of community engagement in local governance (Prehoda et al, 2019).…”
Section: Case Studies Of Community Engagement In Local Governance In ...mentioning
confidence: 99%
“…In Africa, community engagement in global health research has been influenced by structural coercion, highlighting the importance of ethical and culturally sensitive approaches (Nyirenda et al, 2020). Furthermore, a qualitative case study approach of a renewable energy company in South Africa investigated community engagement within the tripartite relationship of a wind farm, the communities, and the local government, emphasizing the significance of collaboration between the private sector, communities, and local government (Robinson & Stephens, 2021). In the USA, communityengaged research experiences in rural communities have demonstrated the integration of collaborative governance for community solar projects, showcasing the practical application of community engagement in local governance (Prehoda et al, 2019).…”
Section: Case Studies Of Community Engagement In Local Governance In ...mentioning
confidence: 99%
“…128 China has been successful in the development of renewable energy projects by improving participation by people in decision making on energy in rural areas. 129 Also, the construction of mini-power plants in Zambia has improved livelihood of local people, 130 as their homes are powered with solar systems. Through the measure, the residents benefit in different ways such as relieving women and children of the time spent in completing household activities manually without the aid of electricity.…”
Section: Addressing the Negative Implications Of Carbon Tax On Human ...mentioning
confidence: 99%